2023
DOI: 10.1039/d3sc01831h
|View full text |Cite
|
Sign up to set email alerts
|

Interface solvation regulation stabilizing the Zn metal anode in aqueous Zn batteries

Abstract: The ethylene carbonate additive regulates Zn anode behavior, enhancing the capacity retention of the full cell (N/P = 1.3) from 51.1% to 80.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This leads to the widely observed HER issue. 39 With the [Zn(H 2 O) 3 (ASA)(SO 4 ) 2 ] 2− structure, on the other hand, the LUMOs dominate on ASA instead of water. This would not only enhance the HER resistivity of solvated water, but also generate an SEI after ASA decomposition on Zn, which further regulates the electrochemical performance of the Zn electrode.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the widely observed HER issue. 39 With the [Zn(H 2 O) 3 (ASA)(SO 4 ) 2 ] 2− structure, on the other hand, the LUMOs dominate on ASA instead of water. This would not only enhance the HER resistivity of solvated water, but also generate an SEI after ASA decomposition on Zn, which further regulates the electrochemical performance of the Zn electrode.…”
Section: Resultsmentioning
confidence: 99%
“…272,273 Symmetric batteries with conventional electrolyte suffer from a gradually increased pH environment, indicating the continuously occurring HER reaction. 101,106,112,274 Therefore, researchers applied an electrolyte additive to maintain the stability of the pH value, which has been described in Section 2.5. 14,101,275 Recently, Zhang et al 107 used a ternary pH ultra-microelectrode (UME, Fig.…”
Section: In Situ Characterizationmentioning
confidence: 99%
“…An efficient way to generate protection layer on Zn electrode is by in situ electrochemical process with electrolyte additives. For example, it has been shown that DMSO 26 and EC 27 molecules are able to enter Zn 2+ solvation structures and create a solid−electrolyte interphase (SEI) on Zn electrode during electrochemical cycling. When enough protection has been provided by SEI, further electrochemical decomposition of additive stops, and the composition and thickness of SEI are stabilized.…”
mentioning
confidence: 99%